Arahan Sistem Perparkiran dalam Pemenuhan Kebutuhan Parkir pada Koridor Perbelanjaan Jalan Sulawesi Kota Makassar - Ramdhany Machmud; Arifuddin Akil; Ihsan Ihsan (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2018)
The availability of inadequate parking facilities and the use of the road body as a parking lot cause traffic congestion along Jalan Sulawesi. This study aims to determine parking capacity, calculate parking requirements, and develop strategic directions to meet parking needs on Jalan Sulawesi. Data collection methods used were observation, interviews, and literature studies. The analytical method used is quantitative analysis, comparative analysis and descriptive analysis. The results of this study indicate that parking on Jalan Sulawesi on weekdays for cars and motorcycles respectively, 327 and 1,110 vehicles / hour. Parking capacity on holidays for cars and motorcycles respectively, 339 and 854 vehicles / hour. Furthermore, parking needs in the Sulawesi Road shopping corridor are based on parking patterns namely, 1,037 Parking Space Units (SRP) for 90º parking, 894 SRP for 60º parking, 819 SRP for 45º parking, 612 SRP 30º parking, and 399 SRP for parallel parking. Directions for meeting the needs of Sulawesi Road parking include, among others, providing parking pockets, applying parking patterns in accordance with parking capacity, conducting socialization related to rules in the parking system, and others.